Analisis Perubahan Kinerja Keuangan Perusahaan yang Melakukan Akuisisi Tahun 2023 - Dwi Luthfiyana; Evaralda Angelica Putri; Alfira Rizka Muktiamalia; Endang Kartini Panggiarti (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
One of the business strategies used by companies to strengthen their business and reduce competition is through acquisitions. This study was conducted to determine changes in financial performance after the acquisition process, measured using liquidity, activity, solvency, and profitability ratios. The population of this study was companies that made acquisitions in 2022. The sampling technique used purposive sampling, and four companies that conducted acquisitions in 2022 and were listed on the IDX were obtained. The research period was two years before and two years after the acquisition. The hypothesis was tested with a non-parametric test using the Wilcoxon signed rank test. Based on the results of the study, it is known that of the four financial ratios, only the activity ratio had a significant difference before and after the acquisition. Meanwhile, there were no significant differences in the liquidity, solvency, and profitability ratios. This is because the impact of the acquisition process cannot be seen in the short term. It takes integration and a long time to create synergy or change after an acquisition.